Content of trace elements in calcic chernozem of fruit agrocenisis - A. V. Kucherenko; O. A. Biryukova (Бюллетень Почвенного института им. В.В. Докучаева, 2025)
Sustainable functioning of fruit agrocenoses and obtaining ecologically clean products are impossible without assessing the microelement content in soils. The paper presents the results of studying the content and distribution of copper, manganese, zinc, iron and nickel in calcic chernozem under cherry (Prunus avium L.) cultivated in the southern horticultural zone of the Rostov region. Soil samples were collected from the following layers: 0– 20, 20–40, 40–60, 60–80, 80–100 cm. The accumulative type of profile distribution with the greatest concentration in the humus-accumulative horizon 0–40 cm was established for all the elements under consideration. The stocks of trace elements in the metre layer of soil were determined. According to content levels Cu, Mn, Zn, Fe and Ni can be arranged in the following decreasing series: gross content – Fe > Mn > Zn > Ni > Cu, mobile forms – Mn > Fe > Cu > Ni > Zn. The share of mobile Cu, Zn, Ni, Fe from their total content in all layers of calcic chernozem is very low and vary from 0.02 to 0.45%, for Mn – from 1.67 to 2.04%. It was revealed that the carbonate content is one of the key factors determining the mobility of trace elements in calcic chernozem. An inverse correlation has been established between the studied mobile compounds of trace elements and the amount of carbonates (for Cu r = –0.88, for Mn r = –0.85, for Zn r = –0.74, for Ni r = –0.85 and for Fe r = –0.84 at p < 0.05). The amount of copper, manganese, zinc, iron and nickel in calcic chernozem in fruit agrocenosis corresponds to regional norms and does not exceed the maximum permissible concentrations.